Identificação de alterações na expressão gênica em carcinomas de pulmão de células não pequenas - Morales, Julia Andrade Pessoa [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Lung Cancer is a leading cause of cancer-related deaths, worldwide. Despite the currently available treatments, patient survival rates within 5 years remain approximately 15%. Recent advances in treatment strategies included the development of therapies with molecular targets, such as the tyrosine kinase inhibitors (TKI) for Epidermal Growth Factor Receptor (EGFR). However, TKI benefit only a fraction of patients with specific histological subtypes of lung cancer. Therefore, the identification of novel, clinically useful targets is urgently needed. The objective of this study is to validate a subset of cancer-related genes in Non-Small Cell Lung Cancer (NSCLC). Primary tumors and histologically normal adjacent lung tissues were obtained from 28 patients who underwent surgical treatment at Botucatu Clinical Hospital, Botucatu, SP. Frozen sections were subjected to RNA extraction and cDNA was synthesized using standard protocols. Gene expression analyzes were performed by quantitative real-time RT-PCR in the QuantStudio 12K system (Life Technologies) for the following genes: EGFR, K-RAS, NOTCH1, SATB2 and ZEB1. Relative gene expression quantification was performed using the Delta Delta CT method, the data was normalized using the endogenous genes B2M and RPS13. Statistical analysis was performed using Wilcoxon paired non-parametric test (GraphPadPrisma v.6.0 software) with statistical significance defined as p<0.05. Overexpression was detected in tumors compared to normal lung samples, as follows: EGFR (p<0.0001), K-RAS (p<0.0001), SATB2 (p<0.0001), NOTCH1 (p=0.027), and ZEB1 (p=0.035). This study confirms that cancer-related genes (EGFR, K-RAS, ZEB1, NOTCH1) are significantly over-expressed in lung cancer samples compared to normal samples. Additionally, SATB2, which have not been previously associated with lung tumorigenesis, was detected as over-expressed. SATB2 regulates gene expression through chromatin structure changes and is suggested to...

O câncer de pulmão é a principal causa de óbitos por câncer no mundo. Apesar das estratégias de tratamento disponíveis, a sobrevida em 5 anos dos pacientes permanece em aproximadamente 15%. Atualmente, avanços nas estratégias de tratamento incluíram o desenvolvimento de terapias com alvos moleculares, tais como inibidores do receptor do fator de crescimento epidérmico (EGFR). Entretanto, essas novas terapêuticas beneficiam uma fração pequena de pacientes com subtipos histológicos específicos da doença. Portanto, é plenamente justificada a realização de estudos moleculares que levem à identificação de biomarcadores com potencial utilidade no tratamento. O objetivo desse projeto é validar um painel de genes associados ao câncer, sendo alguns deles especificamente associados aos carcinomas pulmonares de células não pequenas (NSCLC). Amostras de tumores primários e tecido histologicamente normal adjacentes ao tumor foram obtidas de 28 pacientes submetidos a tratamento cirúrgico no Hospital de Clínicas de Botucatu, SP. O RNA foi extraído e o cDNA foi sintetizado a partir das amostras de tecido congeladas seguindo protocolos padrão. A análise quantitativa da expressão dos genes EGFR, K-RAS, NOTCH1, SATB2 e ZEB1 foi realizada pela metodologia da PCR quantitativa em tempo real no equipamento QuantStudio 12K (Life Technologies). A análise dos dados seguiu o método Delta Delta Ct . Os dados foram normalizados com os genes endógenos B2M e RPS13. Análises estatísticas foram conduzidas utilizando o teste pareado não paramétrico de Wilcoxon (GraphPad Prisma v.6.0 software) com significância estatística definida como p<0,05. Expressão relativa aumentada foi detectada em amostras tumorais comparadas a normais para os genes: EGFR (p<0,0001), K-RAS (p<0,0001), SATB2 (p<0,0001), NOTCH1 (p=0,027), e ZEB1 (p=0,035). Esse estudo confirmou que a expressão gênica de genes associados ao carcinoma pulmonar; EGFR, K-RAS, ZEB1...
Identification of alterations in gene expression in non-small cell lung cancer
Keywords: Pulmões - Câncer; Expressão gênica; Reação em cadeia da polimerase; Marcadores bioquímicos; Biochemical markers